Perfil de usuários e financiamento da acupuntura em um hospital de ensino no interior paulista - Segarra, Sandra (2016)
World Health Organization recognition of Integrative and Complementary Practices (PICs) and the high costs of biomedicine have encouraged countries to implement PICs in their Public Health Systems, since PICs require simplified technological resources and work in the promotion, prevention, treatment, and rehabilitation of most common illnesses, leading to the humanization of treatment. In Brazil, the insertion of these practices in the Unified Health System (SUS) was made possible in 2006, when the National Policy for PICs (Política Nacional de Práticas Integrativas e Complementares or PNPIC in Portuguese) was approved, aiming at broadening treatment at all levels while focusing on primary care. Among the PICs, acupuncture is highlighted due to its popularity and progressive acceptance in western society. Objective: To investigate the profile of acupuncture users and the financing of acupuncture sessions in a teaching hospital in the countryside of Sao Paulo state. Methods: This quantitative, descriptive and traversal study used, as a data source, all records computerized between 2010 and 2016 regarding 2,564 patients who received 19,034 acupuncture sessions as prescribed therapeutic interventions. The data were analyzed using descriptive statistics, the Mann-Whitney U test, the ANOVA test, the Games-Howell Multiple Comparison procedure, Pearson's correlation test, and Multiple Correspondence Analysis (multivariate approach) in order to investigate the relationship between the collected variables, the total number of sessions, and the total financial cost of acupuncture. Results: Most patients were female- 1952 (76.13%), were housekeepers-739 (28.82%), had elementary school education-1077 (42.00%), and were Catholics-1651 (64.39%). The mean number of acupuncture sessions was 7.42 with a standard deviation of 8.99 sessions and a median of 5.0 sessions. The mean financing round for the performance of acupuncture sessions was 91.99 Brazilian Reais/patient with a standard deviation of 120.10 Brazilian Reais and a median of 56.52 Brazilian Reais, reaching a maximum of 1429.06 Brazilian Reais. The mean financing round per session was 12.15 Brazilian Reais, with a standard deviation of 3.74 Brazilian Reais and a median of 14.13 Brazilian Reais, reaching a maximum of 21.47 Brazilian Reais per session. Conclusion: There is a need to offer other healthcare practices provided for in the PNPIC, and show that these practices, their benefits, and the government financing of PICs should be better publicized to users of the UHS and primary care providers, especially physicians.